PROBLEM-BASED LEARNING: A LEARNING METHOD IN IMPROVING STUDENTS’ ENGLISH WRITING SKILLS IN ISLAMIC EDUCATION, UNIVERSITAS MUHAMMADIYAH LAMPUNG - Zohri hamdani; Roldan C. Cabiles (JURNAL PENELITIAN PENDIDIKAN SOSIAL HUMANIORA, 2023)
The purpose of this study was to determine whether implementing problem based learning as a learning method could improve the English writing abilities of students at the Islamic Education program, Universitas Muhammadiyah Lampung. This is an action study with three stages. The sample group consisted of 21 students, and the information was gathered using cluster sampling, test, and an average score. The discoveries of the research demonstrate that problem based learning improves students' English writing abilities, This indicates problem-based learning is beneficial.